Effects of non-steroidal anti-inflammatory drugs on the prevalence of fetal structural malformations (Research, Society and Development, 2020)
Objective: To evaluate the use of non-steroidal anti-inflammatory drugs (NSAIDs) in the prevalence of structural congenital malformations (CM). Methods: Case-control study carried out in a public hospital that is a reference in fetal medicine. A questionnaire was applied to assess sociodemographic and obstetric factors. The evaluation of fetal morphology was performed through ultrasound evaluation. Results: Of the 282 pregnant women evaluated, 28.72% (81/282) reported use of anti-inflammatory drugs during pregnancy, 75.1% (n = 60) of the case group and 25.9% (n = 21) of the group. group control. Among the anti-inflammatory drugs, the most used were nimesulide (17.38%; n = 49), diclofenac (10.99%; n = 31) and ibuprofen (3.19%; n = 9). The use of NSAIDs in general and specific (nimesulide, diclofenac, ibuprofen) did not differ between groups. However, the highest use of ibuprofen was observed in the case group (4.46%; n = 9) vs control (0%; n = 0) with OR = 7.904, p = 0.05. The use of NSAIDs was higher in pregnant women who had fetuses with CM on the face (55.6%), abdominal wall (38.10%) and central nervous system (CNS) (30.30%). Conclusion: Although there were no differences between groups, the use of NSAIDs was considerable in patients who had a fetus with fetal malformations of the face, abdominal wall and CNS. Due to the high frequency of some malformations, especially those of the face, care should be taken with the indication and especially with the self-medication of this medication class during pregnancy.